Proposal for a description system of musical types used in the printing of Spanish incunabula and post-incunabula liturgical books - López Carral, Alicia (Revista General de Información y Documentación, 2024)
Printers tried various techniques to improve quality and reduce printing costs. However, little information is available on the specific methods used to print music during this period, as well as on the different variants and the printers who employed each method. From the 19th century to the present, several scholars have proposed systems of description for the movable type used in early printed liturgical books. However, due to the unique characteristics of music printing, these systems suffer from technical shortcomings. In this paper we will go to type description systems and movable musical types and propose a new description method to investigate it.
Keywords: Book; Liturgical; Musical; Typography; System; Measurements